The effect of discovery learning assisted by interactive media on students' ability to analyze short stories - Herman Didipu; Clarina S.M. Kombu; Amelia Lamadi; Nur Asma A. Kikis (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This research is driven by students' limited ability to analyze short stories, due to the dominance of conventional methods and the limited use of learning media. The purpose of this research is to test the effectiveness of the Discovery Learning model, supported by interactive media (Wordwall and Prezi), in improving students' short story analysis skills. This study uses a mixed-methods approach with an embedded design, combining quantitative data from tests with qualitative data from observations and teacher field notes. The research subjects were 42 ninth-grade students from SMP Negeri 1 Tomilito, divided into experimental and control groups. The quantitative analysis showed a significant improvement in the experimental group, with a mean gain score (M = 22.19), which was much higher than in the control group (10.23 points). Qualitative findings reveal that integrating interactive media can visualize abstract literary concepts, enhance focus, and stimulate student enthusiasm through gamification, despite minor technical challenges at the outset of implementation. The implications of this research affirm that the integration of technology serves as essential scaffolding in literature learning, and provide recommendations for teachers to adopt this model as an innovative solution to enhance students' higher-order thinking skills.